Climate change and original sin : the moral ecology of John Milton's poetry - Cox, Katherine, 1986- (Under the sign of nature., 2023)
"Establishes the primal connection between climate change and human moral transgression as a fundamental ground-theme of Milton's poetry. This book merges perspectives from the history of science, environmental humanities, and literary criticism to situate Milton's depiction of human climate responsibility amid a shifting landscape of seventeenth-century attitudes toward the atmosphere"--